"And I surrender to maternity": a poetic autoethnographic inquiry into juggling roles of a doctoral student mother during the pandemic. Issue 2 (3rd April 2023) - Quynh Phan, Anh Ngoc
ABSTRACT: The juggling roles of doctoral student mothers have worsened since the COVID-19 pandemic ravaged the whole world. While researchers have been focusing on how faculty mothers are burdened by and cope with the "new normal", little attention has been paid to the situation of doctoral student mothers. This autoethnographic poetic inquiry presents a series of poems written when I was experiencing mother guilt for not spending enough time with my two young children during the social distancing time while trying to work on my doctoral research project. Through my autoethnographic poetry, a picture of emotions will be presented, through which I aim to connect my personal responses to a wider audience, including female doctoral students who have children and share similar experiences of being both guilty as a mother and stigmatised as a graduate student amidst the global health crisis.